AGAMA DAN SOLIDARITAS SOSIAL DI ERA INDUSTRI 4.0 DAN MASYARAKAT 5.0 - Abdul Aziz; Halimatus Sa'diyyah; Abu Hasan Mubarok; Kukuh Wibowo; Adistia Octaliadi; Kania Soraya; Karkus Mehan; Suryo Dwi Pranoto (LP2M Universitas Ibrahimy, 2022)
This article aims to examine the phenomenon of religion and social solidarity in digital technology innovation on internet platforms where there are many oblique responses to religion which in the future are considered less attractive and the number of adherents and followers is certain to decrease, especially the millennial generation. Meanwhile, social solidarity that is formed in acts of mutual help and friendship is not directly related to religion, but because these traditions and culture have become the legacy of previous generations. Therefore, it is worth studying in depth in this paper by using a qualitative paradigm approach and exploratory descriptive analysis methods by reviewing related literature. The results found that the existence of Internet technology and other devices makes it easier for religions and their adherents to carry out worship practices by their religious orders, such as online hospitality and helping each other quickly respond through digital networks. Post-secularization religious awareness increased because alienation in the era of disruption made the spiritual void need to be filled with religious values.